Can You Lend Me a Hand? Task-Role Alignment of Social Support for Aspiring Business Owners. (August 2013) - Kim, Phillip H.; Longest, Kyle C.; Aldrich, Howard E.
Previous research has emphasized the positive impact of supportive informal relations on workers in various occupational settings. Such support seems particularly important for workers who aspire to be self-employed, running their own businesses. Existing theory, however, offers little guidance regarding the mechanisms through which these supportive relationships operate. We argue that social support and role expectation theories address this conundrum. Our framework highlights the differences between instrumental and informational support types, the requirements involved in delivering such support, and the benefits of aligning role expectations with the type of support requested. Analyzing a representative sample of people attempting to create their own businesses in the United States, we find evidence consistent with our predictions: social support's effect on people's persistence depends on alignment between the tasks performed and the roles of support providers. To the extent that the support is task-role aligned, aspiring business owners receive the greatest benefits from high-commitment service and labor assistance provided by family and low-commitment informational assistance from friends but also suffer the most when such support is misaligned. These findings cast doubt on the prevailing assumption in the broader social support literature: that having more support always leads to better outcomes.